2015
DOI: 10.1007/s10897-015-9832-x
|View full text |Cite
|
Sign up to set email alerts
|

Support Desired by Women Following Termination of Pregnancy for a Fetal Anomaly

Abstract: With the rapidly evolving field of prenatal testing, there is a growing need to provide support for women pursuing termination of pregnancy following the discovery of a fetal anomaly. Previous studies have documented that women in this situation often feel unsupported, but the type of resources desired by this population remains undetermined. We studied the awareness and utilization of support resources in 51 women at the time of the procedure, at 6 weeks, and at 3 months following the event. Though largely kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 28 publications
(34 reference statements)
3
38
1
Order By: Relevance
“…Adjustments were made as necessary for the specific needs of the respondents in this study. These adjustments were derived from the international literature and from the clinical expertise of the researchers.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Adjustments were made as necessary for the specific needs of the respondents in this study. These adjustments were derived from the international literature and from the clinical expertise of the researchers.…”
Section: Methodsmentioning
confidence: 99%
“…A more recent study demonstrated high levels of grief in women up to 6 months following a TOP for a fetal anomaly despite the use of adaptive coping strategies . Ramdaney et al found that at 6 weeks and 3 months after TOP, many women reported that they were not coping as well as they had anticipated. They were unaware in advance of what psychosocial support they would like to receive and felt unprepared for the psychological consequences of the TOP.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations